Peranan Badan Perencanaan Pembangunan Daerah Terhadap Pelaksanaan Instruksi Menteri Dalam Negeri Nomor 70 Tahun 2021 Tentang Penyusunan Dokumen Perencanaan Pembangunan Daerah Bagi Daerah Dengan Masa Jabatan Kepala Daerah Berakhir Pada Tahun 2022 - Maryam Maryam (Pelantar Press, 2023)
This research was conducted by the author aims to determine the the role of the Regional Development Planning Agency in the Implementation of the Instruction the Minister International Domestic Number 70 Year 2021 concerning the Preparation of Regional Development Planning Documents for Regions with the Service of Regional Heads ending in 2022. The data collection technique was through observation studies, interviews and direct documentation at the Pekanbaru City Regional Development Planning Agency The results of this study can be seen that the Instruction of the Minister International Domestic Number 70 of 2021 has the function and role as a guide and functions to regulate the entire development planning process in Pekanbaru City Bappeda. Pekanbaru City Bappeda is the implementing element of government affairs in the field of planning, where the effectiveness of Bappeda's role is in accordance with Lawrence M. Friedman's theory, namely for the effectiveness of the role three main elements are needed, namely structure, substance and culture. Pekanbaru City is one of the regencies/cities that carry out the Instruction of the Minister of International Domestic Number 70 year 2021, because the term of office of the Mayor and Deputy Mayor of Pekanbaru ends on May 22, 2022. In the midst of the vacancy of the regional head, Pekanbaru City is led by an Acting (Pj.) Mayor, Inmendagri 70 Year 2021 is a tool that serves as a guide for the Pekanbaru City Government, especially Bappeda as an institution that has the authority in the planning sector to compile the Pekanbaru City Regional Development Plan document for 2023 – 2026